Arborealism, or do novels do trees?. Issue 9 (2nd September 2022) - Schoene, Berthold
ABSTRACT: What makes a realist novel an arborealist novel? What does narrative and, in particular, what does the novel need to learn or unlearn in order to 'do' trees? This article looks at two contemporary novels – Annie Proulx's Barkskins (2016) and Richard Powers' The Overstory (2018) – whose main interest has shifted from predominantly portraying human affairs to mobilising a more-than-human eco-narratological dynamic. By invoking the possibility of a plant-led creative impetus, their arborealist outlook and orientation take the traditional novel form out of its realist comfort zone and probe its deeply-ingrained anthropocentric limitations. Following a critical review that examines a wide range of ideas about vegetal agency, and the communicative and inscriptive capabilities of plants, Proulx is shown to experiment with arborealism within the paratextual framework of her novel, while Powers appears embarked upon a full-on, state-of-the-art instantiation of the arboreal sublime.